(untitled) (Research, Society and Development, 2021)
Leishmaniasis is neglected diseases; the drugs used have significant toxic effects that compromise patient compliance, and increased loss of efficacy due to increased resistant infectious strains. Assays on Swiss mice infected with Leishmania brasiliensis and treated with Angiotensin-Suppressing Enzyme (ACE) inhibitors showed that, in addition to the classical effects on the cardiovascular system, some of these inhibitors had effects on nonhemodynamic, immunomediated functions such as cytokine production. In this study, the effect of enalaprilate on nitric oxide (NO) production and cytokines were evaluated, i.e., interleukins-10 and 12 and IFN-γ in J774 A.1 macrophages infected by Leishmania braziliensis. Enalaprilate demonstrated in vitro immunomodulatory capacity, increasing the release of NO to induce IL-12 and IFN-γ also decreasing il-10 release.